MiR-122-5p promotes peritoneal fibrosis in a rat model of peritoneal dialysis by targeting Smad5 to activate Wnt/β-catenin pathway. Issue 1 (31st December 2022) - Liu, Yirong; Ma, Zhihong; Huang, Zhenxing; Zou, Dongmei; Li, Junbin; Feng, Ping
Abstract: Peritoneal fibrosis (PF) is the main reason leading to declining efficiency and ultrafiltration failure of peritoneum, which restricts the application of peritoneal dialysis (PD). We aimed to investigate the effects and mechanisms of miR-122-5p on the PF. Sprague-Dawley (SD) rats were infused with glucose-based standard PD fluid to establish PF model. HE staining was performed to evaluate the extent of PF. Real-time fluorescence quantitative polymerase chain reaction (RT-qPCR) and fluorescence in situ hybridization (FISH) were performed to measure the expression level of miR-122-5p. Western blot was used to test the expression of transforming growth factor (TGF)-β1, platelet-derived growth factor (PDGF)-A, Fibronectin 1 (FN1), extracellular matrix protein 1 (ECM1), Smad5, α-smooth muscle actin (SMA), collagen type 1(COL-1), Vimentin, E-Cadherin, Wnt1, β-catenin, p-β-catenin, c-Myc, c-Jun, and Cyclin D1. Immunohistochemistry (IHC) staining was used to detect type I collagen alpha 1 (Col1α1), α-SMA, and E-Cadherin expression. We found PF was glucose concentration-dependently enhanced in peritoneum of PD rat. The PD rats showed increased miR-122-5p and decreased Smad5 expression. MiR-122-5p silencing improved PF and epithelial–mesenchymal transition (EMT) process in PD rats. MiR-122-5p silencing attenuated the activity of the Wnt/β-catenin signaling pathway. Importantly, dual-luciferase reporter assay showed Smad5 was a target gene of miR-122-5p. Smad5 overexpression significantly reversed the increases of PF and EMT progression induced by miR-122-5p overexpression. Moreover, miR-122-5p mimic activated Wnt/β-catenin activity, which was blocked by Smad5 overexpression. Overall, present results demonstrated that miR-122-5p overexpression showed a deterioration effect on PD-related PF by targeting Smad5 to activate Wnt/β-catenin pathway.